Monty Python and the Holy Grail (Culver City, CA Columbia TriStar Home Entertai, 2001)
This "cult classic" comedy fro the Monty Python team loosely follows the legend of King Arthur ( Graham Chapman), along wit his squire (Terry Gilliam) and his knights of the Round Table as they embark on a fearless quest in search of the elusive Holy Grail.
Keywords: King Arthur; Knights